Determination of replicate composite bone material properties using modal analysis. (February 2017) - Leuridan, Steven; Goossens, Quentin; Pastrav, Leonard; Roosen, Jorg; Mulier, Michiel; Denis, Kathleen; Desmet, Wim; Sloten, Jos Vander
Abstract: Replicate composite bones are used extensively for in vitro testing of new orthopedic devices. Contrary to tests with cadaveric bone material, which inherently exhibits large variability, they offer a standardized alternative with limited variability. Accurate knowledge of the composite's material properties is important when interpreting in vitro test results and when using them in FE models of biomechanical constructs. The cortical bone analogue material properties of three different fourth-generation composite bone models were determined by updating FE bone models using experimental and numerical modal analyses results. The influence of the cortical bone analogue material model (isotropic or transversely isotropic) and the inter- and intra-specimen variability were assessed. Isotropic cortical bone analogue material models failed to represent the experimental behavior in a satisfactory way even after updating the elastic material constants. When transversely isotropic material models were used, the updating procedure resulted in a reduction of the longitudinal Young's modulus from 16.00 GPa before updating to an average of 13.96 GPa after updating. The shear modulus was increased from 3.30 GPa to an average value of 3.92 GPa. The transverse Young's modulus was lowered from an initial value of 10.00 GPa to 9.89 GPa. Low inter- and intra-specimen variability was found.